PENGARUH FEE AUDIT, INTEGRITAS AUDITOR, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA PALEMBANG - Widhah Raihanah; Evada Dewata; Rosy Armaini (EKSISTANSI, 2022)
TheIpurpose of this study is to determine the effect of audit fee, auditor integrity, and time budget pressure on audit quality at public accounting firms in Palembang. The type of data used in this research is quantitative. The population of this research is auditors who work at Public Accounting Firms in Palembang which are registered at the Indonesian Institute of Certified Public Accountants in 2020 as many as 10 KAPs. By using the total sampling method or census obtained 8 KAP as research samples. The data collection of this research was done by distributing questionnaires to 45 auditors. This study uses multiple linear regression analysis with SPSS version 26. The results show that: (1) Audit fee significantly positive effects on Audit Quality (2) Auditor Integrity significantly positive effects on Audit Quality (3) Time budget pressure significantly negative effects on Audit Quality, and (4) Audit Fee, Auditor Integrity, and Time budget pressure together (simultaneously) significantly positivexeffect on Audit Quality by 45.50%.